Gender Inequality Through Language Use in Korean Drama Series When Life Gives You Tangerines - Salsabila Fairu Mufida; Tri Rina Budiwati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to describe the linguistic units used in the dialogues between characters that reveal differences in men’s and women’s language use, and to analyze the contextual meanings and gender inequality that appeared in the Korean drama series When Life Gives You Tangerines. This research is categorized as a descriptive qualitative study employing a sociolinguistic approach, specifically drawing on the theories of Peter Trudgill (2000) and Janet Holmes (2013). The data, in the form of phrases, clauses, and sentences that represent gender inequality, were taken from the selected dialogues in the series and analyzed through identification, classification, and interpretation, based on Judith Lorber's (2001) framework. The study found that, based on the contextual meaning of two phrases, six clauses, and four sentences, a patriarchal ideology exists in Korean society. Furthermore, the analysis reveals that gender inequality is evident in the Korean drama When Life Gives You Tangerines. These include unequal access, economic gaps, political underrepresentation, and societal stereotypes.